Analisa Dampak Lalu Lintas Pada Ruas Jalan Tambak Wedi Surabaya Akibat Rencana Pembangunan Cable Car/ Gondola - Kurnia Hadi Putra; Pradimas Nur Cahyo; Mutiara Firdausi; Nafilah El Hafizah (Jurnal Teknik Sipil, 2022)
The plan to develop a cable car/gondola on Tambak Wedi Road in Surabaya has triggered trip generationand attractions, which can eventually decrease the performance of this road. Therefore, an analysis of the road performance due to the development of the cable car/gondola is necessary to minimize the impact of its performance and to provide solutions to traffic problems when the analysis indicates bad results. This research employed the method of the Manual Kapasitas Jalan Indonesia (MKJI 1997), or Indonesian Highway Capacity manual, and other related regulations. The analysis of road performance began with a traffic survey and was followed by predicting trip generation and attraction. After analyzing the existing conditions of road performance, the researcher analyzed the traffic predictions during construction and operation as well as proposed recommendations for alternative management to overcome the traffic impacts caused by the planned development. The research results demonstrated that the existing condition on Tambak Wedi Road obtained the highest result in the morning by V/C Ratio 0.16 and LOS A, whereas during the construction, the highest result occurred in the morning by V/C Ratio 0.2 and LOS A. Finally, during the operation, the highest result also occurred in the morning by V/C Ratio of 0.57 and LOS A.